FACILITATING CLINICAL SKILL TRAINING DURING AND FOLLOWING THE COVID-19 PANDEMIC - Ide Pustaka Setiawan; Lukas Daniel Leatemia; Fundhy Sinar Ikrar Prihatanto (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2022)
Background: Student skill learning requires a lecturer as a learning facilitator. Lecturers play an important role in facilitating student learning as good observers and listeners, motivators, providing constructive feedback and facilitating reflection.Gaps: The COVID-19 pandemic is a new challenge in medical education. Learning that was previously delivered face-to-face was forced to turn into a full online. What are the facilitation techniques for learning clinical skills and providing feedback during and following the COVID-19 pandemic?Recommendation: During the COVID-19 Pandemic, clinical skill learning can use video conferencing software, augmented reality and virtual reality. Modification of Peyton's facilitation technique can be used in the context of the COVID-19 pandemic. A hybrid method (online and offline) is recommended by considering the government policies. It is necessary to pay attention to the principle of providing constructive feedback to help the student learning process. These new adaptations of the teaching and learning process may be continued following the pandemic.